Educação de surdos indígenas em uma comunidade Pankararu no interior de Pernambuco: educação bilíngue, educação inclusiva ou o quê? - Silva, Bruno Henrique da (Universidade Federal de São Carlos, 2019)
This work presents the reality of the education of indigenous deaf people from a Pankararu ethnic community, located in the interior of the state of Pernambuco, based on interviews with two deaf people and their families. We discussed, from the reports of family members and the difficulty of interviewing the indigenous deaf students themselves in LIBRAS, how education for these students has been proposed in the village (quite distantly from what is provided for by the legislation, specifically by law 10.436 of 2002 and by Decree 5,626 of 2005, which ensure the recognition of LIBRAS as a language and guarantee the access of deaf people to education). Questioning the ways in which the education of the deaf indigenous of this Pankararu community has been carried out, based on the studies of bilingual education for the deaf and the work of the professional translator and interpreter of LIBRAS in the educational sphere, we intend to highlight how much the training of professionals (including and mainly indigenous) in this sense, so that inclusive bilingual education can, in fact, take place within indigenous communities.
Education of indigenous deaf people in a Pankararu community in the interior of Pernambuco: bilingual education, inclusive education or what?
Keywords: Educação bilíngue para surdos; Educação de surdos indígenas; Tradução e Interpretação de LIBRAS na esfera educacional; Educação escolar indígena; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; LINGUISTICA, LETRAS E ARTES::LINGUISTICA